Overcoming Academic Challenges: The Role of Self-Efficacy in Reducing Student Burnout in PAI Learning - Elok Veronika; Hasan Baharun; Abdul Wahid Zaini (Journal of Social Studies and Education, 2024)
This study aims to examine the influence of self-efficacy in overcoming academic burnout among students. The phenomenon of academic burnout that occurs in students in both schools shows a decrease in learning motivation and excessive anxiety about exams and academic assignments. This study uses a qualitative approach with a case study design to understand the factors that affect self-efficacy and burnout among students. The data collection techniques used were in-depth interviews with 15 students, direct observation, and documentation. The collected data was analyzed using the Miles and Huberman analysis model, which included the stages of data collection, data reduction, data presentation, and conclusion drawn. The results of the study show that self-efficacy plays an important role in helping students overcome academic burnout. Factors that strengthen students' self-efficacy include successful experiences, social support from teachers and peers, and a positive mindset developed in facing academic challenges. The implications of this study show that increasing self-efficacy can be an effective strategy in reducing academic burnout and increasing student learning motivation. This research makes an important contribution to the development of education policies in religious schools, emphasizing the importance of a more holistic approach to students' psychological well-being in the face of academic pressure.